Mengusung Politik Damai Abdurrahman Wahid dalam Mengatasi Eskalasi Konflik Kelompok Kriminal Bersenjata dengan Tentara Nasional Indonesia di Papua - Letsoin, Yetva Softiming; Baunsele, Oktovianus Robertus; Taroreh, Tomy (JPP (Jurnal Politik Profetik), 2023)
This paper intends to reflect philosophically as well as to promote the need for a peaceful politics in resolving the conflict of the Armed Criminal Group (KKB) in Papua. This elaboration is reviewed based on Wahid's words and political legacy. The methodology used is the analysis of the text through critical reading that listens to the understanding and concept of peaceful politics according to the spark of Wahid's thought. The author assumes that the prolonged conflict that occurs in Papua, namely the conflict stirred up by the KKB, is one of the biggest threats to the integrity of the Republic of Indonesia. The Indonesian government's decision to upgrade the KKB's status as a terrorist group presupposes the deployment of security forces to hunt down KKB members. However, this has not been the right solution, because in fact the conflict continues to this day. Therefore, the government needs to promote appropriate and relevant solutions so that the disintegration of the nation does not occur. The author finds that humanism and Wahid's ideas about the politics of peace that adhere to the principles of equality and liberation can stem various social and political problems, especially the escalation of conflict in Papua.